2017
DOI: 10.1002/adom.201700654
|View full text |Cite
|
Sign up to set email alerts
|

Broadband, Ultrafast, Self‐Driven Photodetector Based on Cs‐Doped FAPbI3 Perovskite Thin Film

Abstract: In this study, a high‐performance photodetector comprised of formamidinium cesium lead iodide (FA1−xCsxPbI3) thin film is developed. The Cs‐doped FAPbI3 perovskite material is synthesized through a simple spin‐coating method, via which FA1−xCsxPbI3 with different Cs doping levels (x = 0.1, 0.15, 0.2, and 0.3) can be obtained. Further optoelectronic characterization reveals that the FA0.85Cs0.15PbI3 photodetector exhibits reproducible sensitivity to irradiation with wavelengths in the range from 240 to 750 nm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 48 publications
5
54
1
Order By: Relevance
“…The X‐ray diffraction (XRD) pattern of the FA 0.85 Cs 0.15 PbI 3 film is displayed in Figure d. In accordance with the reported literature, the main diffraction peaks with Cs doping level of 0.15 can be indexed to black phase of FAPbI 3 . Figure e presents the XRD of the Bi 2 Se 3 film, from which a series of (0 0 n ) ( n = 3, 6, 9, 12, 15, 18) diffraction peaks belonging to space group of R3̅m/D3 5d (JCPDs No.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The X‐ray diffraction (XRD) pattern of the FA 0.85 Cs 0.15 PbI 3 film is displayed in Figure d. In accordance with the reported literature, the main diffraction peaks with Cs doping level of 0.15 can be indexed to black phase of FAPbI 3 . Figure e presents the XRD of the Bi 2 Se 3 film, from which a series of (0 0 n ) ( n = 3, 6, 9, 12, 15, 18) diffraction peaks belonging to space group of R3̅m/D3 5d (JCPDs No.…”
Section: Resultssupporting
confidence: 81%
“…A schematic diagram of the TI based perovskite photodetector is presented in Figure a, in which a Cs‐doped FAPbI 3 thin film was coated directly on two parallel Bi 2 Se 3 thin films. The Bi 2 Se 3 film is comprised of quintuple layers of Se‐Bi‐Se‐Bi‐Se along the c axis, which has two different forces, weak van der Waals interactions between each quintuple layer (QL) and strong covalent bonding within each QL . The detailed fabrication process is illustrated by a flowchart in Figure S1 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…But this photodetector inevitably have slower response speed relative to other devices, which greatly limits their further development. Luo et al reported a fast‐response formamidinium cesium lead iodide (FA 1 − x Cs x PbI 3 ) photodetector and used a one‐step spin coating method to synthesize OIHP films . When x is equal to 0.15, the photodetector can obtain continuous OIHP thin film with high quality the R and D * of the FA 0.85 Cs 0.15 PbI 3 photodetector are calculated to be 5.7 A W −1 and 2.7 × 10 13 cm Hz 1/2 W −1 respectively.…”
Section: Photoconductive Photodetectorsmentioning
confidence: 99%
“…C, The single normalized cycle of a photodetector used to estimate the rise and fall time. Source : Reproduced with permission from Reference Copyright 2017, John Wiley and Sons…”
Section: Photoconductive Photodetectorsmentioning
confidence: 99%
“…Considering that the concentration of Cs can directly influence the morphology/structure and consequently the optoelectronic properties of Cs‐doped FAPbI 3 perovskite, three samples with different Cs doping levels ( x = 0.1, 0.15, and 0.2) were prepared and compared in this study. Although the diffraction peaks in the X‐ray diffraction (XRD) patterns for the FA 1− x Cs x PbI 3 samples could be all assigned to the black phase of FAPbI 3 , their field emission scanning electron microscopy (FESEM) images are obviously different, as shown in Figure S1 (Supporting Information). In the case of x = 0.1 or 0.2, discontinuous perovskite films with apparent holes and defects were obtained, whereas when x was equal to 0.15, compact and continuous films with a high quality were formed (Figure S1a–c, Supporting Information).…”
Section: Resultsmentioning
confidence: 94%